PENGARUH PROFESIONALISME DAN ENTREPRENEURSHIP TERHADAP KINERJA GURU DI SD CITRA BERKAT CITRALAND SUARABAYA - jurnalpps pps; Yudhar Hapsari Risdiantini; Indra Prasetyo; Fatimah Riswati (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
ABSTRACT National education aims to develop the ability and build the character and civilization of the nation, which is dignified in order to educate the life of the nation. The performance of a teacher is said good if the teacher has done the elements of professionalism that include a high commitment to teaching tasks, mastering and developing learning materials, discipline in teaching and other tasks as well as the need to develop themselves by improving the spirit of entrepreneurship through the development of creativity in the implementation of teaching, cooperation and communication with all the school member, the leadership of teachers who become role models of students, good personality, honest, and objective in guiding students, and responsibility for the task. The teacher performance cannot be separated from learning outcomes, because the teacher's performance is crucial to the success of an effective and efficient learning process. The goal of education can be achieved and materialized from student learning outcomes that ultimately quality graduates. The variables of professionalism and entrepreneurship together significantly affect the performance of teachers, the two independent variables can be used to estimate or predict teacher performance variables. Keywords: professionalism, entrepreneurship, teacher performance